The role of Wnt signaling pathway in mammalian retinal development - Liu, Hong (University of Ottawa (Canada), 2007)
Intercellular communication via secreted signaling molecules is essential for the generation of a normally patterned central nervous system (CNS). The mammalian retina, which is neuroectoderm derived, is an excellent model system in which to study signaling events in patterning, cell proliferation and diversification in the CNS. Although the identity and function of some signaling molecules that regulate retinal development are known, the function of many others, especially members of the Wnt family, has yet to be well characterized. Wnt ligands have been established as critical regulators of multiple developmental processes in a variety of organs and tissues during embryogenesis. To ascertain the function of Wnt signaling in the context of retinal development, I examined the expression of Wnt pathway components in the mouse neural retina. I showed that Wnt2b (formerly known as Wnt13), Wnt receptors and Wnt antagonists are expressed within and adjacent to the distal part of the eyecup, the ciliary margin (CM). beta-gal staining in the eyes of TCF/Lef-LacZ mice, a canonical Wnt pathway reporter mouse strain, revealed the highest level of reporter activity in the CM throughout retinal development. Thus, I hypothesized that canonical Wnt signaling plays a role in the specification and formation of the CM and its derivatives. To test the above hypothesis, I used several approaches to activate Wnt signaling in retinal explants from TCF/Lef-LacZ reporter mice. Ectopic expression of Wnt2b did not activate Wnt reporter activity, while over expression of Wnt3a, a well-characterized canonical Wnt pathway activator, induced reporter gene expression in the CM, but after a considerable delay. Treatment with lithium, a well-known Wnt pathway agonist, resulted in rapid upregulation of Wnt reporter activity, and alterations in morphology and gene expression that were consistent with induction of a CM identity. The expression of stabilized beta-catenin, the key mediator of canonical Wnt pathway activation, was then targeted to the peripheral retina by using a Cre-loxP approach. These transgenic mice exhibited a dramatic increase in beta-catenin-dependent signaling, as well as an expansion of the CM/ciliary epithelium in Cre-expressing region of the retina. Taken together, the findings presented in this thesis indicate that beta-catenin-mediated signaling can promote the development of the CM and its derivatives.
Keywords: Biology, Molecular.; Biology, Neuroscience.; Biology, Animal Physiology.